An anonymous authentication protocol for vehicle to grid based on elliptic curve cryptography - Sun, Zeyu; Wang, Yan (Frontiers in Physics, 2025)
As an important component of the smart grid, Vehicle-to-Grid (V2G) can achieve bidirectional exchange of data and power flow between electric vehicles and smart grid, and is an effective promoter for grid storage and decarbonization. However, when electric vehicles are connected to the grid, the V2G network involves a large amount of privacy data exchange and sensitive charging and discharging transactions. Once these data are leaked, the privacy and security of users will be threatened. The existing authentication protocols in V2G network lack sufficient protection for vehicle user identity privacy and cannot provide user identity anonymity. Therefore, this article proposes an anonymous and privacy-preserving authentication protocol tailored for V2G environments, aiming to protect user identity privacy. The protocol integrates Elliptic Curve Cryptography (ECC) and Physical Unclonable Function (PUF) to achieve mutual authentication between EVs and the grid. It ensures the anonymity of participants through the use of temporary identity values and secures the session key.T he security and efficiency of the protocol are verified through Scyther simulation and heuristic analysis. Compared with other protocols, the protocol proposed in this article not only meets the security requirements in smart grid environment, but also reduces costs, demonstrating significant security and overhead advantages. This work contributes to building a more trustworthy, scalable and privacy-conscious V2G network, thereby supporting sustainable energy development and smart grid security.